Physiochemical changes in physical activity in the immune system to prevent corona virus in football players - Baiji , Muzaffar Oraibi; Alwihed, Raheem Abd; Taherh , Hamad Lahmood; Yasser, Imad Kadem (International Journal of Psychosocial Rehabilitation, 2020)
The practice of physical activity is of multiple benefits, including strengthening the immune system by increasing the effectiveness of the blood circulation that contributes to chemical and physical changes in many of the body’s systems, including the immune system and through physical activity, the body needs greater quantities than normal to bridge the deficiency in which it is active. Minor and major blood circulation, as well as an increase in horizontal and vertical breathing processes, as well as an increase in the oxidized blood pressure to meet the need of working muscles, and therefore there is a clear change in the speed of improvement of the immune system from foreign bodies and the speed of disposal in proportion to the type and size of For the UFOs, the Corona virus is one of the most dangerous foreign bodies that cause harm or death to humans. The practice of physical activity for a period of (20-30) minutes daily contributes to improving the immune system and helps prevent this virus and other foreign bodies.